2011
DOI: 10.4037/ccn2011462
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Prevention Protocol: Decreasing Postoperative Pneumonia in Heart Surgery Patients

Abstract: BackgroundPostoperative pneumonia contributes to morbidity and mortality in patients who have open heart surgery.ObjectivesTo determine if measures to reduce aspiration in patients after cardiothoracic surgery would decrease the occurrence of postoperative pneumonia.MethodsAll patients undergoing cardiothoracic surgery from April 2008 through October 2008 were prospectively enrolled in the study. An aspiration prevention protocol was developed and implemented in a 24-bed intensive care unit. The protocol incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
0
19
0
6
Order By: Relevance
“…Studies have examined general prognostic indicators of swallowing function in different diseases. These indicators include: age [20,21]; severity of the disease [22-24]; cognitive status [18,25]; dysphagia severity level at hospital admission and/or discharge [22,26-28]; presence of feeding tube [29]; time to achieve oral feeding status [14,17,30]; time to tracheostomy weaning [14,31]; ventilator status [17,25]; amount of treatment [14,18,26]; and length of hospital stay [12,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined general prognostic indicators of swallowing function in different diseases. These indicators include: age [20,21]; severity of the disease [22-24]; cognitive status [18,25]; dysphagia severity level at hospital admission and/or discharge [22,26-28]; presence of feeding tube [29]; time to achieve oral feeding status [14,17,30]; time to tracheostomy weaning [14,31]; ventilator status [17,25]; amount of treatment [14,18,26]; and length of hospital stay [12,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Bacterial colonization of oropharyngeal tissues and dental plaque are major precursors to the development of respiratory infection [39]. Implementing protocols to prevent aspiration and improve oral hygiene reduces the occurrence of PP in patients after cardiac surgery [40,41]. Although simple comparisons are not appropriate because of differences in the definition of PP and study populations among previously reported studies, the reported incidence of PP after cardiac surgery is between 2% and 10%, especially during the first week after surgery [42].…”
Section: Oral Hygiene and Postoperative Pneumoniamentioning
confidence: 99%
“…Some studies have evaluated the efficacy of strict perioperative oral management in patients undergoing cardiac surgery. Starks and Harbert [40] reported that the incidence of PP after cardiothoracic surgery was 11% before implementation of an aspiration prevention protocol that included strict oral care; after implementation of the protocol, no patients developed PP. Bergan et al [41] reported in their single-arm prospective intervention study that the incidence of PP following cardiac surgery was 8% (18/226 patients who underwent valve surgery or CABG) after improvement in perioperative oral health through tooth-and tongue-brushing instruction and routine oral rinsing with chlorhexidine gluconate.…”
Section: Oral Hygiene and Postoperative Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…A intubação prolongada, descrita na literatura como uma intubação que se mantém por um período superior a 48 horas 1 ; gravidade da doença de base 22,23,24 ; estado cognitivo 18,25 ; gravidade da disfagia no momento da admissão hospitalar e/ou alta hospitalar 22,26,27,28 ; presença da sonda de alimentação 29 ; tempo para iniciar a alimentação por via oral 14,17,30 ; tempo para a decanulação da traqueostomia 14,31 ; estado ventilatório 17,25 ; quantidade de tratamento 14,18,26 ; tempo de permanência hospitalar 12,32 .…”
unclassified